Restoring Esthetics and Function in Worn Anterior Teeth Using Dahl Principle – A Case Series - S M, Karthickraj; Durrani, Farhan; Bhochhibhoya, Amar; Boyapati, Ramanarayana (Journal of Nepalese Prosthodontic Society, 2025)
Tooth wear due to pathological attrition and erosion is a growing concern in adult patients, often leading to rapid loss of tooth structure without sufficient time for natural reparative processes. Restorative management in such cases requires careful consideration of etiological factors, including bruxism, dietary habits, saliva composition, and gastric regurgitation. This case series presents the use of a cemented Dahl appliance as a conservative and effective method for gaining interocclusal space to restore lost anterior tooth structure. Three patients exhibiting varying degrees of anterior tooth wear and occlusal changes were treated using the Dahl principle, employing a fixed anterior bite platform worn for six months. This appliance facilitated space creation through relative intrusion of anterior teeth and passive eruption of posteriors, enabling definitive restorations using porcelain veneers and crowns. Clinical outcomes were assessed over a two-year follow-up period based on parameters such as plaque and gingival indices, pulp vitality, hypersensitivity, occlusal re-establishment, secondary caries, and mechanical complications. All patients successfully regained posterior occlusion and showed stable gingival and periodontal health. Minor veneer debonding and staining were observed but managed without significant impact on esthetics or function. No cases exhibited hypersensitivity, pulp changes, or occlusal discomfort. The cemented Dahl appliance proved to be a predictable, minimally invasive alternative to more extensive orthodontic or prosthodontic interventions, offering a safe and esthetically favourable solution for patients requiring anterior tooth rehabilitation.